Preparation and Standardization of Mixed Vegetable - Singh, Sauce J P; Nayyer, Md Abu; Kumar, Vinod (Journal of Postharvest Technology, 2014)
The aim of the present work was to utilize the surplus  vegetables for the preparation of sauce. For this, a sum of nine  treatments combining different vegetables was used to prepare  the sauce following the standard method. The vegetable used  were potato, carrot, bottle gourd, palak, coriander, green chilli,  pumpkin, beetroot, cabbage, cauliflower, and bean. The TSS,  total solids, and acidity were increased irrespective of the  combination whereas the sensory attributes were tended to  decrease during the storage. The combination 5 [pumpkin (28%),  beetroot (28%), cabbage (17%), palak (17%), coriander (5%), and  green chili (2%)] has been found the best among the all  combination and treatments. Considering the organoleptic  attributes, the cost benefit ratio of the C5 was 1:2. The results  suggest that the unmarketable vegetables could be used for value  addition especially during glut to have better remuneration.